OYO Rooms: Their Hospitality and Customer Satisfaction - Sharma, Shobha; Nidhi, Nidhi; Pathak, Smita; Pandey, Rudresh; Tianen, Wang; Hung, Daisy Kee Mui; XiaoLin, Huang; Xuan, Wang Ying; Rana, Virat; Naresh, Prudhvi; P.V, Ranjith (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The study is being done on the problems faced by the hospitality and tourism industries. Their growth and development. But here the research is done specifically in respect to OYO. The objective here is to tell the growth story of OYO room in the most objective way possible as a "situation case". One of the efforts has been to provide a body of information of sufficient size to analyse the reasons for the current success of OYO room in particular and the emerging Indian business model of innovative use of technology and marketing principles. The case presents the successful story of the entrepreneur Ritesh Aggarwal, about how he used the idea of hospitality and hotels that generated a significant investment in this segment. The government is in action is focusing on "Make in India", which means that entrepreneurs like Ritesh Aggarwal will be encouraged and supported. It is necessary to create a comfort zone for the young minds so that they can become successful businessmen, leading to the economic growth of the country. So, this Project Report is being prepared by researching the problems faced by the OYO regarding its hospitality and customer satisfaction and its marketing. There are some particular solutions that are recognized by our team for the respective problems which will be useful for the hospitality and tourism industries to overcome certain problems. These solutions will open the doors for the industries that are going to be in this field referring the past data analysis of OYO which is studied and prepared by our team in this Research Project.